Evidence for crustal contamination in intra-continental OIB-like basalts from West Qinling, central China: A Re–Os perspective. (February 2015) - Li, Xiaowei; Li, Jie; Bader, Thomas; Mo, Xuanxue; Scheltens, Mark; Chen, Zhenyu; Xu, Jifeng; Yu, Xuehui; Huang, Xiongfei
Highlights: The degree of partial melting exerts the first-order control on the variation of Os for the DVRs. The crustal contamination is confirmed by the Re–Os system for the DVRs. AFC modeling can reproduce the observed isotopic variations of the DVRs. Abstract: The magnitude of crustal contamination in intra-continental OIB-like basalts is commonly difficult to assess in terms of major, trace-element and Pb–Sr–Nd isotopes. However, the Re–Os isotope system is a very sensitive tracer of the crustal component during formation of basaltic rocks. Here we report new Sr–Nd–Pb–Os geochemical and isotopic data from the Cretaceous Duofutun Volcanic Rocks (DVRs) of West Qinling, central China. The DVRs exhibit low Os abundances (4.46–42.02 ppt) with Re abundances ranging from 45.58 to 812.98 ppt, variably high Re/Os (3–126), and high initial 187 Os/ 188 Os ratios (0.2112–0.6784). We propose that the degree of partial melting is responsible for the first-order control on the variation of Os concentrations. Even the least radiogenic sample still possesses a higher initial 187 Os/ 188 Os ratio than the primitive upper mantle, implying a non-negligible contribution from high Re/Os and 187 Os/ 188 Os reservoir(s). Both the crust and pyroxenite-rich mantle are reliable candidates, but the latter cannot be reconciled with the Os mass balance between pyroxenite and ambient peridotite. Hence, we contend that these rocks were contaminated by crustal materials en route to the surface. Assimilation/fractional crystallization modeling manifests the observed isotopic variations can be produced by minor assimilation of the Proterozoic mafic lower crust. In addition, the intra-continental OIB-like basalts show a relatively wider range of 187 Os/ 188 Os ratios in comparison with MORB and OIB, confirming the continental crust can have a higher concentration of radioactive Os, which is induced by time-integrated growth.